Adult vaccination as part of a healthy lifestyle: moving from medical intervention to health promotion. (17th February 2019) - Doherty, T. Mark; Del Giudice, Giuseppe; Maggi, Stefania
Abstract: As the global population ages, there is concern about the effect of an increased proportion of older individuals on the economic sustainability of healthcare systems and the social effects of an older society. Health authorities and advocacy groups in countries at the forefront of this trend are now developing strategies to ameliorate the social and financial effects of an ageing population. There is broad agreement that for both society and for the individuals, it is important to ensure that increasing lifespans are matched with increased "healthspans" – the number of years spent in good health. There is also growing consensus that vaccination is one of the tools that can play an important role in improving adult health – though currently vaccination coverage is often poor. This review focuses on two issues that consistently appear to be associated with under-vaccination: the low awareness of risk (and potential consequences) for vaccine-preventable diseases and a poor understanding of the value of improved vaccination coverage for adults. We suggest that understanding of vaccination as a health-promoting activity, rather than a medical intervention designed to prevent the spread of a specific pathogen – is a crucial step to improve vaccination uptake among adults (seeSupplementary video abstract ). Key messages: As populations age globally, we are seeing an increasing burden of vaccine-preventable disease in adults. Adult vaccination against some common diseases has been shown to dramatically improve health and quality of life for older people. Despite the attested benefits, vaccination coverage is almost always poor in adults, even in countries where access is free at point of care. In this article, we discuss what appears to a neglected issue in adult vaccination, that of personal autonomy. We argue that adult vaccination will only be successful if it respects individual autonomy and that this requires treating the choice to vaccinate as a public health issue akin to smoking cessation, exercise and healthy diet.